Cape Verdean Transnationalism, Old and New - Meintel, Deirdre (Anthropologica, 2022)
Transnationalism is by no means as recent a phenomenon as many writings on the subject would lead one to believe. The study of Cape Verdean migration over almost two centuries reveals the existence of transnational lifestyles in the nineteenth century; similar findings have been reported for Italian and Chinese migration. Periodizing the history of Cape Verdean migration helps reveal how today’s transnationalism differs from that of the past. Among other things, today’s transnationalism is more diversified and characterized by more intensive contact across diasporic communities. Most importantly, today’s "transmigrants" are playing new political roles and have a different relation with the Cape Verdean nation-state than their predecessors. Such differences cannot be explained by technological advances in transportation and communication alone. Rather, they must be seen in light of broader political and economic changes both in the country of origin and elsewhere.